Influence of the efficacy values on the condition of winner or loser in a Water Polo World Championship - Francisco M. Argudo Iturriaga; Encarnación Ruiz Lara; J. Arturo Abraldes Valeiras (FEADEF, 2010)
This study aimed to find the efficacy values in the playing micro-situations with or without ball possession in the sport of water polo and to analyze the relation between these values and the condition of winner or loser. The female and male matches of the X Water polo World Championship were video-recorded, out agreed by consensus between trained specialists, continuing the directors of the observational methodology. The playing micro-situations were evaluated by means of coefficients such as numerical equality, counterattack, defensive adjustment, simple temporary numerical inequality and penalty, thereby obtaining efficacy values. Data analysis was carried out by an ANOVA of a single factor followed by the Tukey test, revealing significant differences in 38 coefficients in the female category and in 46 coefficients in the male category; reference value was p d» 0.05. In conclusion, we can say that in the female category there are significant differences between the condition of winner or loser in twelve in numerical equality, twelve in counterattack and defensive adjustment, fourteen in simple temporary numerical inequality and none in penalty. In male, there are significant differences between the condition of winner or loser in twelve in numerical equality, eight in counterattack and defensive adjustment, fourteen in simple temporary numerical inequality and twelve in penalty.